Effects of Subcutaneous Repository Corticotropin Gel Injection on Regulatory T Cell Population in Noninfectious Retinal Vasculitis. (16th March 2023) - Anesi, Stephen D.; Chang, Peter Y.; Maleki, Arash; Manhapra, Ambika; Look-Why, Sydney; Asgari, Soheila; Walsh, Marisa; Drenen, Kayla; Foster, C. Stephen
ABSTRACT: Aim: To evaluate the effect of repository corticotropin injection (RCI) on regulatory T cell population in patients with noninfectious retinal vasculitis. Patients and Methods: Patients with active noninfectious retinal vasculitis were included in a prospective nonrandomized open-label study. Results: Eighteen patients (33 eyes) were included in the study. Eleven (61.1%) patients [20 (60.6%) eyes] and 7 (38.9%) patients [13 (33.3%) eyes] were in the responsive and non-responsive groups, respectively. We did not find any statistically significant difference within the PPP-R group, within the PPP-NR group, or between these two groups in regard to regulatory T cell population. No significant systemic or ocular complications were found. Conclusion: RCI may be a complementary treatment in patients with non-infectious retinal vasculitis with or without uveitis. This study did not demonstrate an increase in regulatory T cell population in patients with noninfectious retinal vasculitis.